2004
DOI: 10.1080/10428190310001624143
|View full text |Cite
|
Sign up to set email alerts
|

Acute Leukemia With Natural Killer Cells Antigens in Brazilian Children

Abstract: Malignancies arising from Natural Killer cells (NK) were described mainly comprising disorders related to large granular lymphocyte expansion. Clinical, morphological and immunophenotypic characteristics of myeloid/NK cell precursor acute leukemia (M/NK-AL) have been mainly described in adult patients. We identified nine children with M/NK-AL precursor cells in a series of 264 childhood acute leukemia diagnosed in our laboratory from consecutive referrals before treatment. CD34 +/-, CD13/33 +, CD11b +, a-MPO +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Differentiation of nonnasal NK-cell lymphomas occurring in the skin or soft tissue from extramedullary AML is particularly important for prognostic and therapeutic decisions. However, in acute lymphoblastic leukemia CD56 expression is relatively rare 134,[145][146][147] . CD56 is also expressed in a subset of T-cells, as well as 5-20% of peripheral T-cell lymphomas [148][149][150][151][152][153] .…”
mentioning
confidence: 99%
“…Differentiation of nonnasal NK-cell lymphomas occurring in the skin or soft tissue from extramedullary AML is particularly important for prognostic and therapeutic decisions. However, in acute lymphoblastic leukemia CD56 expression is relatively rare 134,[145][146][147] . CD56 is also expressed in a subset of T-cells, as well as 5-20% of peripheral T-cell lymphomas [148][149][150][151][152][153] .…”
mentioning
confidence: 99%
“…They concluded that the patient had features of both myeloid/NK cell precursor acute leukemia and precursor NK lymphoblastic leukemia/ lymphoma, which suggested an NK-lineage leukemia entity forming a diagnostic continuum. Pombo-de-Oliveira et al [6] also reported a case without CD7 expression among nine cases of myeloid/NK cell precursor acute leukemia.…”
Section: Discussionmentioning
confidence: 91%
“…Th e blast cells in a small proportion of ALL/LBL express CD56 and lack B-, T-, and myeloid-associated markers, do not show Ig and TCR gene rearrangements and are negative for EBV [79][80][81] . Th ey are CD45 dim and may express CD2, CD7, TdT, and/or CD16, and often lack cytoplasmic azurophilic granules.…”
Section: Nk-cell Lymphoblastic Leukemia/ Lymphomamentioning
confidence: 99%